PEMBAKUAN MUSHAF UTHMANI - Muhammad Najib (UIN Raden Mas Said Surakarta, 2016)
In the Muslim’s Scholar, codification’s history and difference of mushaf is a historical fact which must be honestly revealed without having any purpose to demolish fundamental doctrine of Islam on the qur’anic authenticities. This study revealed that Mushaf Uthmani beganfrom the second codification at the period of and by Uthman ibn Affan, meant as an effort to the uniformity of mushaf among Muslim communities. The second codification did not simply copy Abu Bakar’s mushaf which was represented as the result of the first codification, but also completing it with the sentences which are not yet recorded. The second codification was followed up by Uthman by releasing policy which obliged the use of mushaf Uthmani as single mushaf. However, this policy did not at once wipe out non-Uthmani’s mushaf, and did not lessen Qur’anic authenticities.